Sentence Structure in English Grammar Study in National Groups (Texas Journal of Philology, Culture and History, 2023)
The aim of the article is to present different approaches to parts of speech classification in the English language. The topic is vital because of the interest to various explanations of the key principles that form the basis of numerous parts of speech classifications in the English language. As the research work is mainly theoretical, we have chosen descriptive and comparative methods of investigation. As a result we have studied H. Sweet's, H. Smith and G. Trager's classifications. Special attention has been paid to some controversial points like the problems of classification of different groups of verbs and "statives". In the future we can compare parts of speech classifications of the languages that belong to the Germanic family applying diachronic and synchronic approaches.